THE NEED FOR AN ACADEMIC AUDIT FOR THE NATIONAL UNIVERSITY OF SAN MARCOS - Baca Huamaní, Yanette Arminda (2016)
This article “The need for an academic audit for the National University of San Marcos” was based on research: “The importance of the Academic Audit for the management of the National University of San Marcos in the 21st century 2012-2014 “. Completed to obtain the degree of Doctor in Accounting and Business Sciences. The results showed that there is a lag of the Universidad Nacional Mayor de San Marcos, due to the deficiencies in the management processes. In particular, regarding the communication of its members on the plans and results of its execution, suggesting the need for an academic audit for the integral evaluation of its processes. The article focuses on the objectives and hypotheses, with a deductive quantitative methodological approach, using the probabilistic statistical method.